The Role of Natural Antibodies to CC Chemokine Receptor 5 in HIV Infection - Venuti, Assunta; Pastori, Claudia; Lopalco, Lucia (Frontiers in Immunology, 2017)
The CC chemokine receptor 5 (CCR5) is responsible for immune and inflammatory responses by mediation of chemotactic activity in leucocytes, although it is expressed on different cell types. It has been shown to act as co-receptor for the human and simian immunodeficiency viruses (HIV-1, HIV-2 and SIV). Natural reactive antibodies (Abs) recognizing first loop (ECL1) of CCR5 have been detected in several pools of immunoglobulins from healthy donors and from several cohorts of either HIV-exposed but uninfected subjects (ESN) or HIV-infected individuals who control disease progression (LTNP) as well. The reason of development of anti-CCR5 Abs in the absence of autoimmune disease is still unknown; however, the presence of these Abs specific for CCR5 or for other immune receptors and mediators probably is related to homeostasis maintenance. The majority of anti-CCR5 Abs is directed to HIV binding site (N-terminus and ECL2) of the receptor. Conversely, it is well known that ECL1 of CCR5 does not bind HIV, thus the anti-CCR5 Abs directed to ECL1 elicit a long-lasting internalization of CCR5 but not interfere with HIV binding directly; these Abs block HIV infection in either epithelial cells or CD4+ T lymphocytes and the mechanism differs from those ones described for all other CCR5 specific ligands. The antibody mediated CCR5 internalization allows the formation of a stable signalosome by interaction of CCR5, β-arrestin2, and ERK1 proteins. The signalosome degradation and the subsequent de novo proteins synthesis determines the CCR5 reappearance on the cell membrane with a very long lasting kinetics (8 days). The use of monoclonal Abs to CCR5 with particular characteristics and mode of action may represent a novel mode to fight viral infection in either vaccinal or therapeutic strategies.